Meningkatkan Kemampuan CALIS Menggunakan Media Flash Card Kelas II SD Inpres Koperapoka 2 Mimika - Julia Haetubun; Marta Betaubun (Yayasan Perguruan Kampus, 2023)
This research is a type of Classroom Action Research (PTK) which aims to solve problems, as well as seek scientific support. The background to this research is that the ability to read and write is something that is very difficult for class II students at SD Inpres Koperapoka Mimika. This research is to answer the following problems: (1) To find out the steps for using flash card media in learning Indonesian Language Subjects for class II students at SD Inpres Koperapoka 2 Mimika Regency; (2) To find out whether there is an increase in the reading and writing skills of Indonesian Language Subjects in students; (3) To find out whether flashcard media can foster students' active learning in learning Indonesian. The results of this research show that there has been an increase in students' reading and writing abilities by using flashcard media. It can be seen that students' reading abilities have increased each cycle, namely in cycle I there were 16 students with a percentage of 80% in the incomplete category and 4 students with a percentage of 20% the complete category in writing so that in cycle II there was an increase to 5 students with a percentage of 25% incomplete and 15 students with a percentage of 75% declared complete. In cycle II there were 13 students with a percentage of 65% in the incomplete category and 7 students with a percentage of 35% in the complete category in reading so that in cycle II there was an increase to 8 students with a percentage of 40% incomplete and 12 students with a percentage of 60% declared complete. The conclusion of this research is that the use of flash card media in learning Indonesian subjects can increase writing and reading activities in class II students at SD Inpres Koperapoka 2, Mimika Regency.